Adenoviral Transfer of Human Aquaporin-8 Gene to Mouse Liver Improves Ammonia-Derived Ureagenesis - Capiglioni, Alejo Matías (2023)
We previously reported that, in cultured hepatocytes, mitochondrial aquaporin-8 (AQP8) channels facilitate the conversion of ammonia to urea and that the expression of human AQP8 (hAQP8) enhances ammonia-derived ureagenesis. In this study, we evaluated whether hepatic gene transfer of hAQP8 improves detoxification of ammonia to urea in normal mice as well as in mice with impaired hepatocyte ammonia metabolism. A recombinant adenoviral (Ad) vector encoding hAQP8, AdhAQP8, or a control Ad vector was administered via retrograde infusion into the bile duct of the mice. Hepatocyte mitochondrial expression of hAQP8 was confirmed using confocal immunofluorescence and immunoblotting. The normal hAQP8-transduced mice showed decreased plasma ammonia and increased liver urea. Enhanced ureagenesis was confirmed via the NMR studies assessing the synthesis of 15N-labeled urea from 15N-labeled ammonia. In separate experiments, we made use of the model hepatotoxic agent, thioacetamide, to induce defective hepatic metabolism of ammonia in mice. The adenovirus-mediated mitochondrial expression of hAQP8 was able to restore normal ammonemia and ureagenesis in the liver of the mice. Our data suggest that hAQP8 gene transfer to mouse liver improves detoxification of ammonia to urea. This finding could help better understand and treat disorders with defective hepatic ammonia metabolism.